Implikasi Kebijakan Sistem Zonasi Dalam PPDB (Perspektif Orang Tua Dan Sekolah) - Rini Werdiningsih (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
The zoning policy in accepting new students (PPDB) aims to provide equal opportunities for students to get a place in schools in an area or zone. With this zoning policy, student acceptance is no longer based solely on grades or academic achievement but also considers geographical factors or distance to school. The aim is to reduce unhealthy competition in admitting students, as well as strengthen the link between the school and the surrounding community. This study aims to describe the implications of implementing the Zoning system from the perspective of parents and schools. The research was conducted using a qualitative approach, the phenomenological method. The results show that research findings show that many parents do not know about zoning policies. The negative impact according to parents is that children cannot go to school as desired. The positive impact of this zoning system is that children whose domiciles are closest to schools are prioritized, save on transportation costs, and at the same time remove favorite schools from a school perspective. The positive impact of the zoning system policy can increase the number of students, the negative impact is that there is a tendency for school quality to decrease because there is no academic selection that can be carried out optimally. Recommendations from this study, it is necessary to socialize the community about the zoning system policy.